Thermal performance of turbulent flow in a solar air heater channel with rib-groove turbulators - Skullong, Sompol; Kwankaomeng, Sutapat; Thianpong, Chinaruk; Promvonge, Pongjet (My University, 2014)
The paper presents an experimental study on turbulent flow and heat transfer characteristics in a solar air heater channel fitted with combined wavy-rib and groove turbulators. The experiments are performed by controlling the airflow rate to obtain Reynolds numbers in the range of 4000 to 21,000. To produce recirculation flow in the tested channel having a constant heat-flux on the upperwall only, the triangular wavy ribs are placed repeatedly on the tested grooved channelwalls. Three test cases of different rib-pitch to channel-height ratios (PR = P/ H = 0.5, 1 and 2) with a single rib-to-channel height ratio (BR = b/H = 0.25) are introduced in the present work. The wavy ribs are placed with the attack angle of 45° relative to main flow direction. There are three types of rib arrangements, namely, rib-groove on the upper wall only, inline rib-groove, and staggered ribinline groove on two principal walls. The experimental result reveals that the combined rib-groove on both the upper and lowerwalls of the test channel provides the highest heat transfer rate and friction factor in comparison with the smooth channel with/without ribs. However, the ribbed-grooved upper wall at PR = 0.5 yields the highest thermal performance. The combined rib-groove turbulator is found to be considerably higher thermal performance than the groove alone. © 2013 Elsevier Ltd.
Keywords: Channel flow; Groove; Rib; Solar air heater; Thermal performance; Turbulator